Case Report: Approaches for managing resistant cytomegalovirus in pediatric allogeneic hematopoietic cell transplantation recipients - Eunkyung Song; Eunkyung Song (Frontiers Media S.A., 2024)
The instructional case is a pediatric haploidentical TCRαβ+/CD19+ depleted allogeneic hematopoietic cell transplantation recipient who developed early onset CMV infection, which was complicated by resistant CMV (both UL97 and UL54) and successfully managed with maribavir and haploidentical CMV-specific T lymphocytes. Novel approaches to resistant CMV infection are reviewed and effective utilization of recent advances in diagnosis and management of resistant CMV in pediatric HCT are highlighted.